"Come together": a thematic analysis of experiences with belonging. Issue 3 (14th August 2020) - Ogundipe, Esther; Sælør, Knut Tore; Dybdahl, Kenneth; Davidson, Larry; Biong, Stian
Abstract : Purpose: The purpose of this paper is to explore, describe and interpret two research questions: How do persons with co-occurring mental health and substance abuse problems, living in supportive housing, experience belonging? How do residential support staff experience promoting a sense of belonging for persons with co-occurring mental health and substance abuse problems, living in a supportive housing? Design/methodology/approach: Individual semi-structured interviews were conducted with five persons with co-occurring mental health and substance abuse problems living in supportive housing in a Norwegian district. In addition, one semi-structured focus group was conducted with nine residential support staff. All interviews were transcribed verbatim and analyzed using thematic analysis. Findings: Analysis resulted in three main themes: "I do not go to sleep in my pajamas", "Do I have a choice?" and "Be kind to each other". Research limitations/implications: More research on how inclusive practices that are commonly described in guidelines actually affect the experience of residents and residential support staff is needed. Practical implications: Practices that incorporate a communal and contextual understanding when assigning supportive housing are warranted. Originality/value: By paying attention to the components of social recovery, this paper provides a nuanced understanding of how persons with co-occurring mental health and substance abuse problems, living in supportive housing, experience belonging. In addition, residential support staffs' experiences with promoting a sense of belonging for this group are explored.